أثر الزيادة السكانية والنمو الاقتصادي على معدلات البطالة في الجزائر-دراسة قياسية خلال الفترة(1991-2020). - بن الحبيب, طه; صماري, عبد السلام (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة البحثية إلى دراسة أثر الزيادة السكانية والنمو الاقتصادي على معدلات البطالة في الجزائر خلال الفترة ( 1991- 2020 )، ولتحقيق ذلك تم استخدام نموذج الانحدار الذاتي للفجوات الزمنية الموزعة (ARDL )، أين خلصت الدراسة إلى وجود علاقة تأثير لكل من الزيادة السكانية والنمو الاقتصادي على معدلات البطالة في الجزائر على المدى القصير والمدى الطويل، وبالتالي وجود علاقة توازنية طويلة الأجل بين المتغير التابع ( معدل البطالة ) والمتغيرات التفسيرية ( النمو السكاني، النمو الاقتصادي )، كما جاءت النتائج معنوية لجميع المتغيرات ومتوافقة مع النظرية الاقتصادية. تصنيف JEL: J11؛O47؛C22 Abstract: This research paper aims to study the impact of population growth and economic growth on unemployment rates in Algeria during the period (1991-2020).to achieve this auto regression Distributed Lag Model (ARDL) was used, where the study concluded that there is an impact relationship for both population increase and economic growth on unemployment rates in Algeria in the short and long term, and thus the existence of a long-term equilibrium relationship between the dependent variable (unemployment rate) and explanatory variables (population growth, economic growth), the results were also significant for all variables and compatible with the economic theory. Jel Classification codes: J11 ;O47;C22
The impact of population growth and economic growth on unemployment rates in Algeria Standard study during the period (1991-2020)
Keywords: نموذج ARDL ; بطالة ; نمو سكاني ; نمو اقتصادي ; الجزائر